Problem-Based Learning Method for Improving the Learning Achievement of Students - Nurlaelah Nurlaelah (research, training and philanthropy institution Natural Aceh, 2023)
The issue with this study is the low levels of student learning outcomes and learning activities in the sample IPS2 individuals. The objective of this project is to raise student learning outcomes and active learning achievement in social studies. PTK, or classroom action research, is the term used to describe this sort of study. Planning, action implementation, observation, and reflection are all phases of research. The information used in this study came from watching student learning outcomes and activities in Social Sciences 2 courses. According to the recapitulation data, the first cycle's average percentage of learning activities was 63.8%, and the second cycle's average percentage was 89.34%. This demonstrates an increase in student learning activities. In cycles I and II, respectively, the average student learning outcome was 42.22% and 71.04%. This demonstrates that social studies 2 student learning outcomes have improved. The minimum completeness score (71.04%) is obtained, according to the recapitulation of learning activities and student learning outcomes using problem-based learning techniques. Thus, applying the problem-based learning method can improve learning outcomes and learning activities of class C1 IPS2 students of the PGMI FAI-UMI Makassar Study Program.